2013
DOI: 10.1104/pp.113.217380
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Dissection of Spatiotemporal Metabolic Shifts in Primary, Secondary, and Lipid Metabolism during Developmental Senescence in Arabidopsis  

Abstract: Developmental senescence is a coordinated physiological process in plants and is critical for nutrient redistribution from senescing leaves to newly formed sink organs, including young leaves and developing seeds. Progress has been made concerning the genes involved and the regulatory networks controlling senescence. The resulting complex metabolome changes during senescence have not been investigated in detail yet. Therefore, we conducted a comprehensive profiling of metabolites, including pigments, lipids, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
249
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(287 citation statements)
references
References 163 publications
(201 reference statements)
32
249
0
2
Order By: Relevance
“…5B). In addition, several genes involved in amino acid metabolism were up-regulated, suggesting an increased flux toward mitochondrial activity and nitrogen mobilization, both of which are cellular processes associated with senescence (Bouché et al, 2003;Li et al, 2006;Breeze et al, 2011;Debouba et al, 2013Watanabe et al, 2013. Similar effects of O 3 stress on central metabolism have been reported previously: changes in the activity and expression of genes and pathways involved in detoxification and redox balance (e.g.…”
Section: O 3 and Herbivory Affect Central Metabolism In Opposite Wayssupporting
confidence: 76%
“…5B). In addition, several genes involved in amino acid metabolism were up-regulated, suggesting an increased flux toward mitochondrial activity and nitrogen mobilization, both of which are cellular processes associated with senescence (Bouché et al, 2003;Li et al, 2006;Breeze et al, 2011;Debouba et al, 2013Watanabe et al, 2013. Similar effects of O 3 stress on central metabolism have been reported previously: changes in the activity and expression of genes and pathways involved in detoxification and redox balance (e.g.…”
Section: O 3 and Herbivory Affect Central Metabolism In Opposite Wayssupporting
confidence: 76%
“…Tissue-specific accumulation of metabolites, representing one of the main contributions to metabolite diversity, is of great interest to plant scientists (Schilmiller et al, 2010;Chan et al, 2011;Watanabe et al, 2013). Metabolic diversity between different tissues might arise from differences in spatial-temporal expression of genes (Kim et al, 2012;Thatcher et al, 2014) and in some cases by duplicate genes that display spatially or temporally distinct expression patterns (Toubiana et al, 2012;Matsuba et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Much of the enormous diversity of specialized metabolites in plants comes from modifications or decorations of core structures by different tailing reactions such as acylation (Bontpart et al, 2015), glycosylation (Bowles et al, 2005), methylation (Lam et al, 2007), and so on (Schwab, 2003). In addition, many studies have revealed that plant specialized metabolites accumulate with tissue specificity (Schilmiller et al, 2010;McDowell et al, 2011;Kim et al, 2012;Toubiana et al, 2012;Watanabe et al, 2013;Dong et al, 2015;Wen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…3; Supplemental Fig. S5), which is considered as a trait of leaf senescence (Watanabe et al, 2013). The excessive sulfate in leaves is a result of the enhanced SO activity that produces sulfate de novo from sulfite generated by the enhanced APR activity ( Fig.…”
Section: Early Leaf Senescence In the Tomato Sir-impaired Plantsmentioning
confidence: 99%